1977
DOI: 10.1161/01.res.41.6.865
|View full text |Cite
|
Sign up to set email alerts
|

Lack of correlation of plasma norepinephrine and dopamine-beta-hydroxylase in hypertensive and normotensive subjects.

Abstract: THE ENZYME dopamine-0-hydroxylase (DBH), which is responsible for the formation of norephinephrine (NE) from dopamine, 1 is released along with the catecholamines from the adrenal medulla 2 and from stimulated sympathetic nerves in perfused organs. "5 The enzyme is present in plasma of man and other animals. 6 In animals, the levels of the enzyme are increased with stress 7 and decreased after chemical destruction of the sympathetic nerve endings but not after adrenalectomy.8 Thus, DBH in plasma appears to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

1980
1980
1994
1994

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…The failure to establish a correlation between DBH activity and its common physiological substrate DA or its metabolic product NE also confirms previous findings that DBH activity is not a reliable index of the degree of sympathetic neuronal discharge of the catecholamines in individuals [15]. As far as DBH activity is concerned CF patients also seem to follow the pattern found in normals, in patients with hypertension and in patients with other chronic diseases [13,15,18].…”
Section: Discussionsupporting
confidence: 82%
“…The failure to establish a correlation between DBH activity and its common physiological substrate DA or its metabolic product NE also confirms previous findings that DBH activity is not a reliable index of the degree of sympathetic neuronal discharge of the catecholamines in individuals [15]. As far as DBH activity is concerned CF patients also seem to follow the pattern found in normals, in patients with hypertension and in patients with other chronic diseases [13,15,18].…”
Section: Discussionsupporting
confidence: 82%
“…The molecular weight of DBH is approximately 290.000 dalton. In the past, plasma DBH has been used as an indi cator of sympathetic activity in nonuremic patients [21] and in uremic patients on hemodialysis or hemofiltration [2,3,8], However, there is conflicting evidence in literature whether acute changes in DBH reflect acute changes of sympathetic activity and whether basal DBH reflects steady state sympathetic tone [21,22], Acute changes in plasma catecholamines are often paralleled [26], although not consistently so [27], by changes in plasma DBH. Such inconsistency may be due to the fact that a major portion of DBH does not enter the circulation by exocytosis of secretory granules, but by 'shedding' of membrane-bound DBH during turnover of axonal plasma membrane con stituents.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in this laboratory [11] and by Lake et al [9] have revealed inconsistent changes in plasma DBH in patients with essential hypertension. However, in chronic pathological denervation of primary idiopathic orthostatic hypotension, plasma DBH and catecholamines were significantly depressed [13].…”
Section: Discussionmentioning
confidence: 63%
“…n = 6 [8] and 228± 10 pg/ml, n = 60 [4], but lower than reported by Lake et at. [9,10] of 304 20 pg/ml, n = 84. As with EPI, the NE levels in hemodialysis patients increase to control levels during the postdialysis period.…”
Section: Resultsmentioning
confidence: 99%